Functional recovery after accidental deep hypothermic cardiac arrest: Comparison of different cardiopulmonary bypass rewarming strategies - Filseth, Ole Magnus; Kondratiev, Timofei; Sieck, Gary C.; Tveita, Torkjel (Frontiers in Physiology, 2022)
Introduction: Using a porcine model of accidental immersion hypothermia and hypothermic cardiac arrest (HCA), the aim of the present study was to compare effects of different rewarming strategies on CPB on need for vascular fluid supply, level of cardiac restitution, and cerebral metabolism and pressures. Materials and Methods: Totally sixteen healthy, anesthetized castrated male pigs were immersion cooled to 20°C to induce HCA, maintained for 75 min and then randomized into two groups: 1) animals receiving CPB rewarming to 30°C followed by immersion rewarming to 36°C (CPB30, n=8), or 2) animals receiving CPB rewarming to 36°C (CPB36, n=8). Measurements of cerebral metabolism were collected using a microdialysis catheter. After rewarming to 36°C, surviving animals in both groups were further warmed by immersion to 38°C and observed for 2 h. Results: Survival rate at 2 h after rewarming was 5 out of 8 animals in the CPB30 group, and 8 out of 8 in the CPB36 group. All surviving animals displayed significant acute cardiac dysfunction irrespective of rewarming method. Differences between groups in CPB exposure time or rewarming rate created no differences in need for vascular volume supply, in variables of cerebral metabolism, or in cerebral pressures and blood flow. Conclusion: As 3 out of 8 animals did not survive weaning from CPB at 30°C, early weaning gave no advantages over weaning at 36°C. Further, in surviving animals, the results showed no differences between groups in the need for vascular volume replacement, nor any differences in cerebral blood flow or pressures. Most prominent, after weaning from CPB, was the existence of acute cardiac failure which was responsible for the inability to create an adequate perfusion irrespective of rewarming strategy.